Bancos comunitários, moedas sociais e políticas públicas: Da experiência pioneira do banco Palmas (Fortaleza-CE) ao modelo difusor do banco Mumbuca (Maricá-RJ) - Sandro Pereira Silva; Camila Amaral Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This paper aimed to problematize the relationship between community development banks (BCDs) and public management. Therefore, we sought to analyze the main elements that allowed this relationship of complementarity, with a case study, based on pioneering experiences, on the factors that guided the evolution of solidarity finance initiatives in Brazilian territory and their insertion in the agenda of governments of different federative units. It was possible to identify that this theme has manifested itself through an innovative operational arrangement, oriented around the elaboration and execution of social policies, although it is not immune to tensions and limits inherent to public administration itself.
10419/284899
Keywords: J54; Z13; 330; Solidarity economy; community development banks; social currencies; local development; governmental agenda